2011
DOI: 10.1016/j.catena.2011.01.011
|View full text |Cite
|
Sign up to set email alerts
|

Secondary minerals from extrapedogenic per latus acidic weathering environments at geomorphic edges, Eastern Nebraska, USA

Abstract: Acidic weathering of the sulfidic Upper Cretaceous Carlile and Pierre Shales in Nebraska has led to the precipitation of the Al sulfate-hydroxide minerals aluminite, alunite, "basaluminite"/felsöbányaite (e.g.,), the aluminum hydroxides gibbsite and bayerite, and the rare Al phosphate hydroxide vashegyite. Kaolinite has also been produced as a result of this acidic weathering. These minerals do not appear as neoformed constituents in any extant soils in the region, and their existence underscores the ability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…The occurrence of these 'exotic' aluminium-bearing salts is interpreted by Chukanov et al (2013) as indicator for feldspar alteration, favoured by exposure to sulphuric acid resulting from oxidation of primary sulphates. Joeckel et al (2011) also concluded that the presence of aluminite (among other Al-bearing sulphates) in the deposits may reflect long-term exposure of rocks or sediments to weathering in natural environments.…”
Section: Implications Of the Formation Of Other Evaporites In The Aro...mentioning
confidence: 98%
“…The occurrence of these 'exotic' aluminium-bearing salts is interpreted by Chukanov et al (2013) as indicator for feldspar alteration, favoured by exposure to sulphuric acid resulting from oxidation of primary sulphates. Joeckel et al (2011) also concluded that the presence of aluminite (among other Al-bearing sulphates) in the deposits may reflect long-term exposure of rocks or sediments to weathering in natural environments.…”
Section: Implications Of the Formation Of Other Evaporites In The Aro...mentioning
confidence: 98%
“…Cluster 3 and Cluster 5 grouped bricks fired at the lowest temperature, probably below 750 • C, marked in particular by the presence of illite and dolomite. They had the most representative brick of the set, samples A05 and B07, respectively (see diffractograms in Figure 6b), and they were distinguished by the peak (~7.79 Å, d-spacing) of Al sulfate-hydroxide minerals aluminite, (Al 2 SO 4 (OH) 4 •7H 2 O), weathering product attributed to the natural reaction of acidic sulfate with clay material [37]. Clusters 1 and 2 grouped bricks fired at a high temperature (above 950 • C).…”
Section: Qzmentioning
confidence: 99%
“…Fibrous Al-sulfate (alunite) formation was only observed experimentally on the mica surfaces exposed to wet O 2 -SO 2 -scCO 2 . The reaction of acid sulfate solutions with phyllosilicates have been suggested to be the source of Al for the formation of alunite, with similar morphology fibrous laths and rosettes in shales in weathering environments (where pyrite oxidation has occurred to provide sulfate) (Joeckel et al, 2011). The model used here is limited to bulk water-rock reactions with dissolved gases, and was not used to model the scCO 2 phase.…”
Section: Accepted Manuscriptmentioning
confidence: 99%